Level Up Your Crisis Management Skills - Aalbers, Rick; McCarthy, Killian; Groen, Arjan (MIT Sloan Management Review, 2026)
Leaders who have successfully managed crises in governments and large organizations aren’t innately better at it. Interviews with high-level leaders in a variety of industries found that people with strong crisis management skills have invested time and effort to develop maturity in seven key areas, dubbed the 7C’s: contingency planning, cross-functional coordination, transparent communication, compassion, confrontation of hard truths, control, and continuity.